PERAN KECERDASAN EMOSIONAL (EQ) DALAM PEMBELAJARAN: STUDI LITERATUR DARI PERSPEKTIF PSIKOLOGI PENDIDIKAN - Yudi Hendrilia; Muhammad Sukron Fauzi; Dwi Hadita Ayu; Archristhea Amahoru; Septi Fitriana (Ekasakti Jurnal Penelitian dan Pengabdian)
The aim of this research is to deeply explore how emotional intelligence (EQ) affects various aspects of learning, including motivation, learning strategies, and social interactions, and to provide evidence-based recommendations on practical ways to integrate EQ development into educational settings. Additionally, this study aims to identify potential areas for further research to expand our understanding of the role of emotional intelligence in the evolving context of education. This research employs a literature review methodology, which involves collecting, analyzing, and synthesizing information from various sources. The findings of this study conclude that emotional intelligence (EQ) plays a crucial role in education by influencing various aspects of the teaching and learning process. EQ, which encompasses the ability to recognize, understand, and manage one's own emotions as well as those of others, is closely related to academic performance, social interactions, and stress management. Developing EQ through training programs and curriculum integration not only enhances student motivation and academic achievement but also improves classroom dynamics and students' ability to handle stress. Recent trends indicate that the implementation of social-emotional programs and EQ training is becoming increasingly common, with results showing improvements in the learning environment and student well-being. By adopting an approach that emphasizes emotional development and social skills, education can create a more supportive atmosphere and better prepare students to face future challenges.